Application of Health Belief Model on Factors Affecting Participation in the National Health Insurance Scheme among Informal Sector Workers in Kudus, Central Java - Anom Dwi Prakoso; Endang Sutisna Sulaeman; Arief Suryono (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Universal Health Coverage is the mandate of the Pancasila and 1945 Constitution. UHC's target on January 1st, 2019 is that all Indonesians are covered by the National Health Insurance (JKN). Meanwhile, the participation of informal workers as of May 1, 2019 only reached 57%. The cross subsidy system is not optimal and the budget deficit will continue to be experienced because there are still many citizens who have not joined JKN. This study aimed to analyze the determinants of the participation of informal workers in the national health insurance program in Kudus using the Health Belief Model.Subjects and Method: This was case control study,conducted in 5 sub-districts in Kudus Regency, Central Java from September to October 2019. Total of 200 informal workers were selected by purposive sampling, it were devided into two groups including 100 in case group and a 100 in control group. The dependent variable was the participation of informal workers in the JKN program. The independent variables were perception of vulnerability, perception of seriousness, perspective of benefits, family support, self-efficacy, and social environment. The data collection was performed using a questionnaire and data analysis with logistic regression using stata 13.Results: The participation of informal workers in the JKN program increased with knowledge of ≥Senior high school (b = 5.09; 95% CI = 0.32 to 9.87; p = 0.036), high perception of vulnerability (b = 3.01; 95% CI = 0.26 to 5.75; p = 0.031), high perceived seriousness (b= 5.38; 95% CI = 2.14 to 8.61; p= 0.001), high perceived benefit (b= 3.86; 95% CI= 0.39 to 7.34; p= 0.029), strong family support (b= 7.26; 95% CI= 2.69 to 11.82; p= 0.002), strong self-efficacy (b = 3.98; 95% CI = 0.98 to 6.98; p= 0.009) and a supportive social environment (b = 4.51; 95% CI= 1.61 to 7.40; p= 0.002).Conclusion:Knowledge, perception of vulnerability, perception of seriousness, perceived usefulness, family support and social environment influence the participation of informal workers in the JKN program.Keywords: universal health coverage, national health insurance, health belief modelCorrespondence: Anom Dwi Prakoso, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: anomdwiprakoso@gmail.com. Mobile: +62895363054393.Journal of Health Policy and Management (2020), 5(1): 61-73https://doi.org/10.26911/thejhpm.2020.05.01.06